Gender and ICTs - Food; Agriculture Organization of the United Nations (United Nations, 2018)
This publication looks at the benefits of Information and Communication Technologies (ICTs) when placed in the hands of men and women working in agriculture and in rural areas. It examines the challenges to be overcome and makes recommendations so that rural communities can take full and equal advantage of the technologies. FAO’s E-agriculture 10 Year Review Report on implementation of the World Summit on the Information Society (WSIS) of the Action Line C7. ICT Applications: e-agriculture concludes that while substantial progress has been made in making ICTs available and accessible for rural communities, challenges remain with respect to the following seven critical factors for success: content, capacity development, gender and diversity, access and participation, partnerships, technologies, and finally, economic, social, and environmental sustainability. This publication analyses with the gender lens the seven factors of success, followed by an overview of the general existing barriers to women’s access to, control and use of ICTs. Finally, it offers a series of recommendations for better integration of gender in ICT initiatives, based on gender mainstreaming throughout the seven critical factors of success, illustrated with concrete examples.